PENGARUH KEPEMILIKAN MANAJERIAL, STRUKTUR MODAL, KEBIJAKAN DIVIDEN, DAN INVESTMENT OPPORTUNITY SET (IOS) TERHADAP NILAI PERUSAHAAN (Studi Pada Perusahaan Sub Sektor Farmasi Yang Terdaftar Di Bursa Efek Indonesia Tahun 2018-2023) - Tiarma Yuliartika Hutauruk; Mahatma Kufepaksi (Nusantara Hasana Journal, 2026)
Managerial ownership is a condition when managers own company shares, so managers act as both managers and shareholders who actively participate in decision-making. Capital structure is the financial proportion of a company between capital sourced from long-term debt and equity, which serves as a source of financing for the company. Dividend Policy is the company's decision regarding whether the profits earned will be distributed to shareholders as dividends or retained as retained earnings to finance future investments. Investment opportunity set generally describes the extent of investment opportunities available to a company. This study aims to determine the effect of managerial ownership, capital structure, dividend policy, and investment opportunity set on firm value. The population of this study consists of pharmaceutical companies listed on the Indonesia Stock Exchange from 2018 to 2023, with a sample of 9 companies selected using purposive sampling technique. The analysis method used is panel data regression analysis using Eviews 13. The research results show that capital structure, dividend policy, and investment opportunity set significantly positive affect the value of the company, while managerial ownership does not significantly affect the value of the company.